The Use of Gamma App as a Learning Aid at SMPN 60 Bengkulu Utara - Warsito Warsito; Parwito Parwito (SMART : Jurnal Teknologi Informasi dan Komputer, 2026)
This article examines the potential and implementation of Gamma App as an innovative learning aid at SMPN 60 Bengkulu Utara. By leveraging artificial intelligence (AI), Gamma App enables teachers to efficiently create interactive learning media, presentations, and documents. This research highlights how the integration of AI technology in the teaching and learning process can enhance learning effectiveness, student engagement, and provide personalized feedback. Through a literature review and analysis of Gamma App's features, this article presents a conceptual framework for utilizing this application in the context of junior high school education in Indonesia, specifically at SMPN 60 Bengkulu Utara. It is hoped that the utilization of Gamma App can support the achievement of more adaptive learning objectives relevant to the needs of students in the digital era.